PUBLIC PRIVATE PARTNERSHIP AND UTILIZATION OF MATERNAL AND CHILD HEALTH SERVICES IN DISTRICT ABBOTTABAD, PAKISTAN - Imtiaz, Ayesha; Farooq, Ghulam; Haq, Zia Ul; Ahmed, Ashfaq; Anwer, Saeed (Journal of Ayub Medical College Abbottabad, 2017)
Background: Public Private Partnership has been experimented as an approach in Pakistan in 2005 and in eighteen districts of Khyber Pakhtunkhwa including Abbottabad in 2011, to improve delivery of maternal and child health services. This study was conducted to assess the utilization of maternal and child health services before and after implementation of Public Private Partnership in district Abbottabad. Methods: A cross sectional study was conducted in district Abbottabad from July to December 2014. Study included all the 53 basic health units, outsourced to People’s Primary Healthcare Initiative in 2011. Data related to selected maternal and child health services indicators (family planning services, antenatal and post-natal care, safe delivery, tetanus toxoid vaccination of pregnant women and child immunization), before and after the introduction of Public Private Partnership, was collected. Significance tests (t-test) was applied and p-value <0.05 was taken as significant. Results: Marked improvement was observed in vaccination of target children (127%) and women (42%), respectively. Similarly, utilization of family planning services, antenatal and postnatal care increased by 60%, 9% and 38%, respectively. Public Private Partnership had significant effect on postnatal visits (p<0.001), family planning services (p<0.001), women vaccinated with tetanus toxoid (p<0.001) and children vaccinated in Expanded Program of Immunization (p=0.003). Conclusion: Public Private Partnership improved the utilization of maternal and child health services, particularly family planning services and maternal & child immunization. The partnership may be scaled up and extended, for an improved coverage of maternal and child health services. Keywords: Pakistan; Public Private Sector Partnership; Primary Health Care; Child Health Services; People’s Primary Healthcare Initiative